Zima naszej goryczy - Steinbeck, John, 1902-1968.; Steinbeck, John, 1902-1968. (Gdansk : Wydawn. ATEXT, 1993)
A contemporary novel by the American Nobel Prize winner.
Translation of: Winter of our discontent.